Innovation of MSMEs in North Sumatra: Integrating Quality Management and the Tetrapreneur Model - Azizah Mudrikah; P. L. Rika Fatimah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, MSMEs in North Sumatra are expected to develop innovation based on quality management and integrated entrepreneurial strategies to enhance competitiveness and business sustainability. However, in reality, many MSMEs still face limitations in implementing systematic quality management and have not optimally integrated the pillars of Creativity, Sustainability, Market Orientation, and Leadership as a comprehensive innovation framework. This study aims to formulate an integrative Tetrapreneur-based model combined with quality management to improve the innovative performance and value creation of MSMEs. The research employs a field-based qualitative approach using a case study design involving MSMEs in North Sumatra, with data collected through interviews, observations, and documentation. Data were analyzed using thematic analysis and source triangulation to ensure validity. The findings reveal that the integration of quality management and Tetrapreneur pillars significantly enhances operational efficiency, product consistency, market adaptability, and sustainable innovation capacity of MSMEs.